Psychoeducational counseling and emotional adaptation of relatives of elderlies at the 'San Camilo' subcenter, year 2020 - Maldonado Cañizares, Paola Robertina; Peñafiel Villareal, Ruth Esther; Muñoz Corrales, Monica Lucrecia; Meza Velez, Felix Leonardo; Jimenez Plaza, Javier (Research, Society and Development, 2023)
This paper addresses aging in the third age as an ongoing developmental process and underscores the importance of considering e as active elderlies members of society, with new roles and contributions. It emphasizes that emotional balance during this stage is crucial, and Psychoeducational counseling is presented as a vital tool to assist individuals in confronting and accepting the challenges of aging. A mixed-method approach was employed, utilizing an inductive-deductive and exploratory methodology. Survey results reveal that a significant proportion of relatives of elderlies report that their loved ones struggle to accept their current situation. This underscores the need to cultivate a positive attitude toward old age and promote the idea that it is a natural phase of life. Psychoeducational counseling programs emerge as an effective solution to enhance the emotional adaptation of relatives of elderlies These programs not only offer psychological support but also contribute to the ongoing inclusion of elderlies in society and in their own final stage of life. This highlights the importance of addressing aging as a process of growth and development during the third age, where Psychoeducational counseling plays a pivotal role in supporting elderlies and their families in their emotional adjustment and acceptance of this life stage.